Investigation of multidrug-resistant plasmids from carbapenemase-producing Klebsiella pneumoniae clinical isolates from Pakistan - Lascols, Christine; Cherney, Blake; Conley, Andrew B.; Rishishwar, Lavanya; Crawford, Matthew A.; Morse, Stephen A.; Fisher, Debra J.; Anderson, Kevin; Hodge, David R.; Pillai, Segaran P.; Hughes, Molly A.; Khan, Erum; et al. (Frontiers in Microbiology, 2023)
Objectives. The study aim was to investigate multidrug-resistant (MDR) plasmids from a collection of 10 carbapenemase-producing Klebsiella pneumoniae clinical isolates identified within the same healthcare institution in Pakistan. We used a combined Oxford Nanopore/Illumina sequencing approach to characterize the AMR content, characteristics and structure of the MDR plasmids, as well as to determine their plasmid-based antimicrobial susceptibility profiles. Methods. Plasmids were isolated from 10 clinical isolates of Klebsiella pneumoniae, and from a corresponding set of Escherichia coli transconjugants, then sequenced using Nanopore/Illumina technology to generate plasmid hybrid assemblies. Full characterization of MDR plasmids, including determination of next generation sequencing (NGS)-based AMR profiles, plasmid incompatibility groups, and types, was carried out. The structure of MDR plasmids was analyzed using the Galileo AMR platform. For E. coli transconjugants, the NGS-based AMR profiles were compared to NGS-predicted AMR phenotypes and conventional broth microdilution (BMD) antimicrobial susceptibility testing (AST) results. Results. All carbapenemase-producing K. pneumoniae isolates carried multiple AMR plasmids (blaNDM-1, or/and blaOXA-48) encoding 34 antimicrobial resistance genes (ARGs) conferring resistance to antimicrobials from 6 different classes. The plasmid incompatibility groups and types identified were: IncC (ST1 and ST3), IncFIA (type 26) IncFIB, IncFII (types K1, K2, K7, K9), IncHI1B, and IncL. None of the blaNDM-1- and blaESBL-plasmids identified in this study were previously described. Most blaNDM-1-plasmids shared identical AMR regions suggesting potential genetic material/plasmid exchange between K. pneumoniae isolates of this collection. The majority of NGS-based AMR profiles from the E. coli transconjugants correlated well with both NGS-based predicted and conventional AST results. Conclusions: This study highlights the complexity and diversity of the plasmid-based genetic background of carbapenemase-producing clinical isolates from Pakistan. This study emphasizes the need for characterization of MDR plasmids to determine their complete molecular background and monitor AMR through plasmid transmission between multi-resistant bacterial pathogens.